A Qualitative Phenomenological study of Emotional and Cultural Intelligence of International Students in the United States of America - Thompson, Rohan (Journal of International Students, 2018)
This phenomenological study examined the role of emotional and cultural intelligence in the social integration of international students. The study included nine participants who were selected using purposeful sampling. The researcher used five main interview questions to guide the datacollection process. The questions were designed to help determine both whether the participant appeared to be competent in cultural and emotional intelligence, and how that competence then contributed to his or her social integration. The study findings revealed that emotional and cultural intelligence played an important role in enabling international students to integrate socially. This article seeks to offer a deeper understanding of the social integration challenges of international students, contribute to the existing knowledge, and offer suggestions for future research.